1999
DOI: 10.1002/(sici)1097-0045(19990601)39:4<316::aid-pros14>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for biopsy outcome in the European Randomized Study of Screening for Prostate Cancer (Rotterdam Region)

Abstract: BACKGROUND In the European Randomized Study of Screening for Prostate Cancer (ERSPC, Rotterdam region), men aged 55–74 years are screened for prostate cancer by prostate‐specific antigen (PSA) sampling, digital rectal examination (DRE), and transrectal ultrasound investigation (TRUS). All men with a PSA ≥4 ng/ml and/or a suspicious DRE and/or a suspicious TRUS are biopsied. METHODS Logistic regression analysis was applied to derive a predictive index that equals the chance to find prostate cancer in a biopsy g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
6

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 16 publications
(16 reference statements)
1
47
0
6
Order By: Relevance
“…Another possible detection bias results from the fact that multiple studies, including the current, found that obese men have larger prostates (23,24,27). Prostatic enlargement would make detection of an existent cancer less likely, given an equal-sized tumor and an equal number of biopsy cores were obtained (32,33). Combining lower PSA concentrations and prostatic enlargement would represent an inherent bias against detecting cancers among obese men.…”
Section: Discussionmentioning
confidence: 86%
“…Another possible detection bias results from the fact that multiple studies, including the current, found that obese men have larger prostates (23,24,27). Prostatic enlargement would make detection of an existent cancer less likely, given an equal-sized tumor and an equal number of biopsy cores were obtained (32,33). Combining lower PSA concentrations and prostatic enlargement would represent an inherent bias against detecting cancers among obese men.…”
Section: Discussionmentioning
confidence: 86%
“…DISCUSSION Earlier studies showed that algorithms based on total PSA, free PSA, DRE and prostate volume can be used to reduce the number of false-positive PSA results in screening for prostate cancer more efficiently than the proportion of free PSA alone. [12][13][14][15][16][17][18][19] Despite this, there are no reports on the use of such algorithms in a prospective setting. Our study included 1,775 screen-positive men from the 3 largest participating centers in the European Randomized Study of Screening for Prostate Cancer, 20 -22 making it the largest study on predicting prostate biopsy results in the PSA range 4 -10 g/l using LR and neural networks.…”
Section: Clinical Stage and Histopathologic Gradementioning
confidence: 99%
“…Combined use of several variables has been shown to reduce the number of false-positive PSA results more efficiently than single use of the proportion of free PSA. [12][13][14][15][16][17][18][19] However, LR or neural network algorithms for prostate cancer detection have not been studied prospectively; i.e., use of algorithm outcomes for making real-life biopsy decisions has not been reported. We simulated a prospective setting by using earlier subjects as training data and later ones for testing of the algorithms.…”
mentioning
confidence: 99%
“…However, up to two-thirds of cancers were missed at the 4 ng/ml threshold. In a community-based study of serial screening, 22% of men older than 50 years with PSA concentrations between 2.6 and 4.0 ng/ml had prostate cancer [27]. In the European Randomized Study of Screening for Prostate Cancer (ERSPC), 36.5% of detectable prostate cancers were identified in the 87.5% of men who had PSA concentrations lower than 4 ng/ml.…”
Section: Screening For Prostate Cancer With Psa (The Test)mentioning
confidence: 99%